Redemption through annihilation?!: Game designer´s views on religion, culture and society and its influences on digital games - Piasecki, Stefan (Online - Heidelberg journal of religions on the internet, 2016)
While video games have been under public observation for approximately 30 years, focus has hardly ever been put on the creators, designers, developers, or other creative staff.The “Game Developer Demographics Report” of the International Game Developers Association (IGDA) from the year 2005 was one of the very few attempts to survey game developers regarding their personal motivation and outlook on life but it explicitly excluded inquiries on religious aspects; even asking about sexual preferences caused considerable complications.Who game designers are and what they think is however not unimportant. Video game players are confronted with ethical and moral decisions, quite often set into a background story with multiple references to religious (or “magical” for that matter) topics. The content and the scope of game-experiences reflect the player´s personal input - based on the game designers ideas and plans and content, shaped by their very own personality.According to Gräb, religion certainly is not confined to churches but permeates other public spheres, the media not being the least of these. Religion still primarily deals with the major issues in life - not only in holy books or movies, but also in video games, which are traditionally settings for myths, enigma, legends and also religion. Hitherto, the following questions remain unexplored: What do game developers think and believe in political and religious matters, what role do they ascribe to themselves and their productions in it? How do developers comprehend their role? This article will present the results of a first explorative study amongst young game developers.